THE DEVELOPMENT OF ZOONOTIC DISEASE PREVENTION EDUCATION MATERIALS FOR ANIMAL SHELTER WORKERS IN KANSAS - Luckenbach, Katya (My University, 2021)
Diseases that result from the transmission of pathogens from animals to humans are referred to as zoonotic diseases. Individuals who work closely with animals on a daily basis have an increased occupational hazard of contracting a zoonotic disease. Holding a position in an animal related field, such as veterinary medicine, often requires an educational background and/or on the job training in zoonotic disease prevention. There are, however, other fields where employees are required to work closely with animals but are not provided adequate training on zoonotic disease prevention. Animal shelter workers and volunteers may be among those who are at the highest risk for contracting zoonotic diseases, yet they are not consistently provided educational materials or tools to help them prevent the spread of disease. While an abundant amount of primary literature has been published on zoonotic disease potential of pathogens commonly carried by dogs, cats, and other animals that might be living in animal shelters, there are arguably, no user-friendly guide books or guidelines designed to train shelter workers on zoonotic disease prevention. This project aims to identify which zoonotic diseases animal shelter workers are most at risk for contracting and to create user friendly educational materials for use in training animal shelter workers.
Keywords: zoonotic disease; animal shelter; shelter medicine; occupational hazzard; public health; staff training